Designing advance care (incapacity) planning and advance directives legislation in British Columbia. Issue 2 (1st June 2012) - McGregor, D; Clelland, C; Barwich, D; Porterfield, P; Hoffmann, C
Abstract : Responding to societal demands, the Province of British Columbia legislators began amending its health care consent and personal planning statutes in 2005, with a particular view to strengthen Advance Care Planning and make Advance Directives a legal option. Initial frameworks met with concern by professional and public organisations and feedback was provided to the Attorney General's office as well as to the Ministry of Health. Province wide consultation with stakeholders informed the new laws which were passed in 2007 and came into force in September 2011. These comprised options for Advance Directives as well as appointment of Substitute Decision Makers (called Representatives). The nature and scope of this collaboration process will be described. Consultations with clinicians, local health care administrators and Advance Care Planning professionals led to a province-wide approach in developing the legislation and regulations, leading to the production of provincially standardised products. These tools include Health Care Provider and Patient and Family guidebooks for developing optional advance care plans, advance directives and representation agreements which do not require lawyer visits. Educational materials (e.g. FAQs, and PowerPoints) have also been developed to educate and upskill health care providers in ACP, and inform them of their responsibilities within the new legislation. This has included the physician community with the development of physician specific materials including a "primer" on the legislation and an ACP video. The process of development of the educational materials and the materials themselves will be shared with participants.